Syriac Hagiography : Texts and Beyond - Minov, Sergey,; Ruani, Flavia, (Texts and Studies in Eastern Christianity ;, 2021)
Chapters gathered in Syriac Hagiography: Texts and Beyond explore a wide range of Syriac hagiographical works, while following two complementary methodological approaches, i.e. literary and cultic, or formal and functional. Grouped into three main sections, these contributions reflect three interrelated ways in which we can read Syriac hagiography and further grasp its characteristics: "Texts as Literature" seeks to unfold the mechanisms of their literary composition; "Saints Textualized" offers a different perspective on the role played by hagiographical texts in the invention and/or maintenance of the cult of a particular saint or group of saints; "Beyond the Texts" presents cases in which the historical reality behind the nexus of hagiographical texts and veneration of saints can be observed in greater details.